2020
DOI: 10.1111/and.13817
|View full text |Cite
|
Sign up to set email alerts
|

Testicular tissue oxidative stress in azoospermic patients: Effect of cryopreservation

Abstract: This study evaluated oxidative stress (OS) in human testicular tissue in obstructive (OA) and nonobstructive azoospermia (NOA) before and after cryopreservation. Azoospermic patients were subjected to surgical sperm retrieval (SSR) and cryopreservation. Assay of catalase activity (CAT) and malondialdehyde level (MDA) using colorimetric methods was done. The number of retrieved spermatozoa and the Johnson score were assessed in fresh testicular samples. The study included 21 OA (group A) and 16 positive sperm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…Such results were not observed in OA patients. Our results are supported by the study of Moubasher et al [34]. They showed that catalase activity increased in testicular tissue from OA patients which was not observed in the NOA group, suggesting that testicular tissue from OA patients can withstand the oxidative stress caused by freezing more than NOA [7].…”
Section: Discussionsupporting
confidence: 90%
“…Such results were not observed in OA patients. Our results are supported by the study of Moubasher et al [34]. They showed that catalase activity increased in testicular tissue from OA patients which was not observed in the NOA group, suggesting that testicular tissue from OA patients can withstand the oxidative stress caused by freezing more than NOA [7].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a study by Mubasher et al ( 38 ) indicates high production of reactive oxygen species in a number of azoospermic subjects with varicoceles. Varicocelectomy has the potential to diminish the reactive oxygen species generation and up-regulates the antioxidant activity of seminal plasma ( 39 , 40 ).…”
Section: Effects Of Varicocele and Varicocelectomy On Sertoli- And Le...mentioning
confidence: 98%
“…Окислительный стресс (ОС) приводит к повреждению сперматозоидов (1, 2) и снижению качества нативной и криоконсервированной спермы (3)(4)(5). Причиной развития ОС становится чрезмерная продукция активных форм кислорода (АФК), истощение антиоксидантных возможностей организма или совокупность этих факторов.…”
unclassified